Stereotactic aspiration alone or Ommaya placement and aspiration followed by stereotactic radiosurgery for cystic brain metastasis: A systematic review and meta-analysis - David R. Peters; Alfredo Conti; Marc Levivier; Luis Schiappacasse; Mohamed Faouzi; Mioara Florentina Trandafirescu; Constantin Tuleasca (Brain and Spine)
Introduction: Cystic brain metastases (BMs) are often more challenging to treat than solid BMs. Stereotactic cyst aspiration for volume reduction followed by stereotactic radiosurgery (SRS) is an alternative treatment modality that may benefit patients with large cystic BMs not favorable for SRS alone nor microsurgical resection. Research question: Here, we perform a systematic review and meta-analysis of stereotactic aspiration alone or reservoir (Ommaya) placement plus aspiration followed by SRS for cystic BMs. Material and methods: Using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, we reviewed articles published between 1968 and December 31−th, 2022. We retained 10 studies reporting 280 patients. Results: Overall rate of tumor control for combined treatment of Ommaya placement plus aspiration plus SRS was 81.2% (62.5–99.9%, p < 0.001) and for stereotactic aspiration plus SRS was 64.7% (46.1–83.3%, p < 0.001). Overall rate of further intervention for combined treatment of Ommaya placement plus aspiration plus SRS was 15.8% (p = 0.08) and for stereotactic aspiration plus SRS was 14.8% (5.3–24.4%, p = 0.002). Overall complication rate for combined treatment of Ommaya placement plus aspiration plus SRS was 12.8% (2.3–23.3%, p = 0.01) and for stereotactic aspiration plus SRS was 1.5% (p = 0.12). Discussion and conclusion: Combined treatment of Ommaya placement plus cyst aspiration plus SRS in cystic BMs yields better local control as compared to stereotactic aspiration plus SRS, with similar rate of further intervention between procedures. Aspiration of the cyst plus SRS should be considered for patients with cystic metastases not able to undergo open surgery or upfront SRS.